Growth and anatomical responses in Xanthostemon chrysanthus as influenced by Paclobutrazol and Potassium Nitrate - Ahmad Nazarudin, M.R.; Tsan, F.Y.; Normaniza, O.; Adzmi, Y. (Universiti Kebangsaan Malaysia, 2015)
A study was conducted to determine the effects of a plant growth regulator (paclobutrazol, PBZ) and commercial fertilizer (Krista-K Plus) as a source of potassium nitrate (KNO3 ) on the growth of Xanthostemon chrysantus. It was also attempted to investigate the anatomical changes in the leaf and stem after the treatment. Nine treatments, i.e. control (no PBZ and Krista-K Plus application),